Necrophagy by the social Wasp Agelaia pallipes (Hymenoptera: Vespidae, Epiponini): Possible forensic implications - Moretti, T. C. [UNESP]; Thyssen, P. J. [UNESP]; Godoy, W. A.C. [UNESP]; Solis, D. R. [UNESP] (My University, 2008)
The occurrence of 62 specimens of Agelaia pallipes caught in carrion traps using three types of baits (fish, cow liver and poultry viscera) in three different types of environments (rural, urban and forest area) in seven municipalities in Southeastern Brazil is reported here. This specific necrophagic behavior is discussed, since investigations concerning carrion wasps are scant in literature.
Keywords: Brazil; Forensic entomology; Swarm-founding wasps; Vertebrate carrion